Nutraceuticals: Modern Era’s Nutritional Pharmaceuticals - Sneha Golani; Garima Jain; Arvind Jadon; Atul Kaushik (Current Research in Pharmaceutical Sciences, 2012)
In recent year there is a growing interest in nutraceuticals which provide health benefit and arealternative to modern medicine. Nutrients, functional food and dietary supplements are majorconstituents of nutraceuticals which make them instrumental in maintaining health, act againstvarious disease condition and thus promote the quality of life. Nutraceuticals hold promise inclinical therapy as they have the potential to significantly reduce the risk of side effectsassociated with therapy along with reducing the health care cost. Nutraceuticals have receivedconsiderable interest because of their presumed safety and potential nutritional and therapeuticeffects”. Nutraceuticals are medicinal foods that play a role in maintaining well being,enhancing health, modulating immunity and thereby preventing as well as treating specificdiseases. The ability of nutraceuticals to positively influence cardiovascular risk factors shouldbe recognized as an enormous opportunity in the treatment of a highly prevalent disease. Theydo not easily fall into the legal category of food and drug and often inhabit a grey area betweenthe two. Risk of toxicity or adverse effect of drugs led us to consider safer nutraceuticals andfunctional food based approaches for the health management. Recent improvements in theidentification and standardization of botanical materials, coupled with screening by human cellline and gene expression-directed fractionation, are expected to expedite the development ofnew nutraceuticals and drugs. These will afford an immediate benefit to the rapidly emergingalternative, complementary, and integrated healthcare practices. It is also hoped that thenutraceuticals industries and regulatory agencies will work together to prevent the ultimate costof new drug development from becoming prohibitive.